Phosphorus utilization in growing pigs fed a phosphorus de cient diet supplemented with a rice bran product and amended with phytase (2010)
ABSTRACT: Rice bran is not only a source of energy for pigs, it also contains significant amounts of phosphorus (P). However, about 75% of this P is not digested by the pig, unless phytase is added to the diet. Once excreted, P may end up contaminating water bodies and thus causing eutrophication. The objectives of this study were to determine the digestibility of P and other nutrients in a diet supplemented with increasing levels of rice bran (0, 7.5, 15, and 30%), and to evaluate the effects of phytase inclusion on the nutrient digestibility of rice bran. Pigs (n= 24, 87.5 ± 2.51kg) were confined in individual metabolic crates to determine total tract apparent digestibility and retention of nutrients. The digestibility coefficients found for dry matter, energy, fat, N, and P in the rice bran product used were: 72, 79, 84, 74, and 15%, respectively. Phytase supplementation increased P digestibility (p<0.01) but it did not increase N digestibility (p>0.1); the increase in fecal P excretion that occurred when rice bran was added to the diet was reduced by 26% with phytase supplementation.